2005
DOI: 10.1111/j.1365-294x.2005.02477.x
|View full text |Cite
|
Sign up to set email alerts
|

Local genetic structure in a clonal dioecious angiosperm

Abstract: We used seven microsatellite loci to characterize genetic structure and clonal architecture at three different spatial scales (from meters to centimetres) of a Cymodocea nodosa population. C. nodosa exhibits both sexual reproduction and vegetative propagation by rhizome elongation. Seeds remain buried in the sediment nearby the mother plant in a dormant stage until germination. Seed dispersal potential is therefore expected to be extremely restricted. High clonal diversity (up to 67% of distinct genotypes) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
63
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 68 publications
6
63
1
1
Order By: Relevance
“…Ziegenhagen et al (2003) 24 reported that small-scale sampling detected new genotypes that had not been found in large-scale sampling. There are also similar reports of small-scale clonal diversity of the seagrass Cymodocea nodosa (Ruggiero et al 2005) and clonal woodland species, such as Anemone nemorosa (Holderegger et al 1998;Stehlik and Holderegger 2000) and Uvularia perfoliata (Kudoh et al 1999). Intermingled parts in the C. keiskei population might include additionally unidentified genotypes than detected at the 5-m sampling scale.…”
mentioning
confidence: 61%
“…Ziegenhagen et al (2003) 24 reported that small-scale sampling detected new genotypes that had not been found in large-scale sampling. There are also similar reports of small-scale clonal diversity of the seagrass Cymodocea nodosa (Ruggiero et al 2005) and clonal woodland species, such as Anemone nemorosa (Holderegger et al 1998;Stehlik and Holderegger 2000) and Uvularia perfoliata (Kudoh et al 1999). Intermingled parts in the C. keiskei population might include additionally unidentified genotypes than detected at the 5-m sampling scale.…”
mentioning
confidence: 61%
“…The presence of these barriers decreases the dispersal, migratory, and reproductive capabilities of individuals and leads to the restriction of gene flow and formation of genetically isolated groups (Slatkin 1987). Although genetic structure has been demonstrated at macrogeographic scales in several seagrass populations (Procaccini & Mazella 1998, Reusch et al 1999, Olsen et al 2004, Muñiz-Salazar et al 2005, there are few studies that demonstrate whether microgeographic genetic isolation occurs (Ruckelshaus 1998, Procaccini et al 1999, Reusch 2002, Billingham et al 2003, Ruggiero et al 2005. Estuaries and coastal lagoons are heterogeneous habitats where physical, chemical, and ecological factors interact with complex dynamics creating spatially discrete and fragmented habitats for most species inhabiting these embayments (Bilton et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Gene flow can act as an evolutionary force that counterbalances the effects of genetic drift, and this may be a simple function of geographic separation between populations or may be influenced by other factors such as dispersal vectors and barriers. Cymodocea nodosa has low dispersal potential, at the scales of tens of meters, as shown by indirect methods using spatial autocorrelation statistics of microsatellite markers , Ruggiero et al 2005; however, the dispersal potential for this species in the Canary Islands remains unstudied. Low dispersal potential leads to the prediction that genetic drift will play the most predominant role in shaping genetic structure of C. nodosa in this archipelago.…”
Section: Introductionmentioning
confidence: 99%